2020
DOI: 10.1007/s10565-020-09544-2
|View full text |Cite
|
Sign up to set email alerts
|

Human hepatic in vitro models reveal distinct anti-NASH potencies of PPAR agonists

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…A significant (5.62 ± 0.78 fold, p < 0.05) upregulation of inflammatory C-X-C motif chemokine 5 (CXCL5) was observed in only MCDM incubated spheroids compared to untreated control. CXCL5 regulates the hepatic recruitment of neutrophils and monocytes during NASH [ 38 ]. Livogrit (30 µg/mL) and pioglitazone (10 µM) treatment normalized (p < 0.05) the expression of this inflammatory cytokine ( Figure 4(d) ).…”
Section: Resultsmentioning
confidence: 99%
“…A significant (5.62 ± 0.78 fold, p < 0.05) upregulation of inflammatory C-X-C motif chemokine 5 (CXCL5) was observed in only MCDM incubated spheroids compared to untreated control. CXCL5 regulates the hepatic recruitment of neutrophils and monocytes during NASH [ 38 ]. Livogrit (30 µg/mL) and pioglitazone (10 µM) treatment normalized (p < 0.05) the expression of this inflammatory cytokine ( Figure 4(d) ).…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the complexity of NASH and its human-specificity, NASH-related research has been largely directed towards human-based technologies in recent years [ 22 ]. To that extent, we recently developed a methodology that can be employed to study NASH in vitro and screen for potential anti-NASH compounds [ 6 , 7 ]. In the present study, we confirmed the clinical relevance of the thus-developed in vitro disease models by whole genome-based pathway analysis using four publicly available datasets of patients suffering from NASH.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that more performant and predictive preclinical models should be employed during the investigation of novel anti-NASH therapeutics. We recently showed that human hepatic in vitro models, including primary human hepatocytes (PHH), human skin precursor-derived hepatic progenitor cells (hSKP-HPC), and HepaRG and HepG2 cell lines, can model key NASH-specific cellular mechanisms and capture potential anti-NASH properties of novel compounds such as peroxisome proliferator-activated receptor (PPAR) agonists, a drug class that is under clinical evaluation for anti-NASH treatment [ 6 , 7 ]. PPARs have a regulatory role in hepatic lipid metabolism and inflammation and multiple dual- and pan-PPAR agonists, which can supposedly lead to a reduction of hepatic lipids and inflammation, are under investigation, including lanifibranor (a pan-PPAR agonist, phase 3, NCT04849728), saroglitazar (a dual PPAR-α/γ agonist, phase 2, NCT03863574), and elafibranor (a dual PPAR-α/δ agonist, phase 3, NCT02704403) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…These successful applications are a consequence of the fact that hSKPs acquire a strong lipid metabolism upon hepatic differentiation to hSKP-HPC. Furthermore, hSKP-HPC recently showed to mimic the anti-steatotic responses induced by a series of PPAR agonists in a similar way as primary human hepatocytes, being the gold standard for hepatic in vitro modelling, emphasizing the position of hSKP-HPC for modelling NASH in vitro [11] . Considering the restricted availability and fragility of primary human hepatocytes, we optimized a flow cytometric method to quantify the anti-steatotic response induced by potential anti-NASH pharmaceuticals in hSKP-HPC.…”
Section: Methods Detailsmentioning
confidence: 99%